An updated checklist of the HORSE FLIES (DIPTERA: TABANIDAE) from Malaysia with a new species and four new records - Hazem Al-Talafha,; Salmah Yaakop,; Idris Abdul Ghani,; Abdulrahim Aljamal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tabanidae fauna of Malaysia consists of 116 species belonging to eight genera. The current study adds one new species and four new records. Tabanus atroflavus sp. nov., was described and the main morphological characteristics were illustrated. The new records were listed, namely Haematopota cilipes Bigot; Tabanus atristylatus Burger; Tabanus inflatipalpis Schuurmans Stekhoven; and Tabanus tonglai Surcouf. A checklist of Malaysian tabanids was provided based on the available scientific literature and material examined